Modeling and Designing of a Novel Lab-scale Passive Solar Still - Hisham A. Maddah (Journal of Engineering and Technological Sciences, 2019)
The solar still is an emerging water distillation technology gaining popularity among the scientific community. Achieving a high throughput and/or performance in solar stills remains an unresolved challenge. In this study, the feasibility of utilizing solar distillation systems for large water production was investigated. A solar still was designed and tested with different brackish waters under solar insolation in Los Angeles from March to April. The inner surface area of the cell was about 12.7 cm  12.7 cm with a maximum volume of 322.6 cm3. The still performance was evaluated experimentally and modeled theoretically, showing a good agreement between theory and experiment. The maximum achieved efficiency was 20.54%, corresponding to a freshwater production of 384.4 mL/day·m2 (6.2 mL/day). Lowering the feed amounts from 120 to 30 mL/day resulted in increasing the experimental performance from 6% to 18.3% due to the quick ramp in heat of vaporization; however, the production rates decreased from 446.4 to 341 mL/day·m2 (7.2 to 5.5 mL/day). Polystyrene insulation and a blackened walls/basin can improve the performance by maintaining high temperature, decreasing heat loss, and enhancing solar absorption. It is concluded that still materials, insolation rate, and inclination angle are the most critical design factors.